Kepemimpinan Kiai dalam Mengembangkan Kurikulum Pendidikan di Pondok Pesantren: (Studi Kasus: Pondok Pesantren al-Rifaie 2 Gondanglegi, Pondok Pesantren Miftahul Ulum Putri Ganjaran, dan Pondok Pesantren Rakyat alAmin Malang) - Yazidul Busthomi (Jurnal Pendidikan Islam, 2020)
Abstract: The main capital that causes a Kiai to succeed indeveloping education in Islamic boarding schools is, in essence,extraordinary knowledge in his leadership in developing education inhis Islamic boarding school. So that education in Islamic boardingschools that are developing at this time is solely dependent on theleadership of the Kiai in developing his education. Based on thedescription of the problem, the researcher raised the title "KiaiLeadership in developing educational curriculum in Islamic boardingschools (case study: Pondok Pesantren al-Rifaie 2 Gondanglegi,Islamic Boarding School Miftahul Ulum Putri Ganjaran, and IslamicBoarding Schools of the People of al-Amin Malang). background of theproblem that has been explained above, then the problem formulationcan be taken, namely: 1. How is the leadership of the Kiai indeveloping the education curriculum at Pondok Pesantren al-Rifaie 2Gondanglegi Malang? 2. How is Kiai's leadership in developing theeducation curriculum at Miftahul Ulum Islamic Boarding School inGanjaran Gondanglegi Malang? 3. How is Kiai's leadership indeveloping an educational curriculum at Pondok Pesantren Rakyat alAmin Malang? In order to obtain truly valid data in this study, theresearcher needs to determine the appropriate data collectiontechniques. Therefore, researchers use the following techniques: 1.Interview techniques, 2. Observation techniques, 3. Documentationtechniques. From the results of research conducted by researchers todescribe the leadership of Kiai in developing an educationalcurriculum in Islamic boarding schools (case study: Pondok Pesantren al-Rifaie 2 Gondanglegi, Islamic Boarding School Miftahul Ulum PutriGanjaran, and Islamic Boarding Schools of al-Amin Malang), it can beconcluded the results of the data namely three Kiai in developingeducational curricula in their respective Islamic boarding schools, bysubmitting to heads of fields or units in developing educationalcurricula, and using responsive leadership models